A framework for subjective motion production: A construal approach with Mandarin evidence - Xinxin Shan; Zaibing Luo; Gengsheng Xiao; Bin Liu (PLoS ONE, 2026)
This study develops and validates an experimental framework for investigating the production of subjective motion sentences (e.g., The road winds through the valley ), a phenomenon that has been examined mainly from comprehension perspectives. Using Mandarin as a case study, we first conducted corpus-based analyses to develop the framework, which incorporates: (1) an analysis of four key construal operations (selection, perspective, prominence, and imagination) together with aspectual construals, (2) a classification for subjective motion sentence types based on aspectual marking and subject traversability, and (3) three experiential motivations (perceiving, scanning, and imaging) used to characterize recurrent construal tendencies in production. Guided by the framework, we designed picture-elicitation tasks and conducted production experiments with native Mandarin speakers to test its validity. The findings demonstrate that the framework effectively elicits diverse subjective motion types, capturing language-specific regularities while pointing to cross-linguistically applicable principles of motion construal. By linking corpus evidence to experimental validation, the study provides a systematic and replicable approach that can be extended to future cross-linguistic research on motion and language.